ILham PENGAMATAN POHON TIDUR SIAMANG DAN GIBBON DI STASIUN PENELITIAN SORAYA SUBULUSSALAM: OBSERVATION OF SIAMANG AND GIBBON SLEEPING TREES AT SORAYA SUBULUSSALAM RESEARCH STATION) - amar, aidil; Reza Ilham Akbar; Syifa Saputra; Reza Fahmi; Munawar (Jurnal Lingkungan Almuslim, 2024)
Abstract, Leuser Management is within the Leuser Ecosystem Area but outside the Leuser National Ecosystem Park. The first research station is Ketambe in the southeastern part and the second research station is Suaq Balimbing in the southern part of Aceh, both of which are in the Leuser Ecosystem Area and are also in the Gunung Leuser National Park (Leuser Management Unit, 1997). Research objectives: To identify the types of sleeping trees chosen by gibbons and gibbons as sleeping places and to analyze environmental factors that influence the choice of these trees as well as observing the sleeping behavior patterns of these two primate species. Results and discussion Daily roaming distance of Siamang Siamang Sleeping Tree Position at the Soraya Research Station The Soraya Research Station in Subussalam, Aceh, is an important location for the study of gibbons and their ecology in their natural habitat. The sleeping gibbon trees at this research station may be a major focus in understanding gibbon behavior and ecology in the region. On the Soraya track trail, shown in Figure IV.1, the yellow track is the waypoint for the siamang as well as the position of the sleeping gibbon tree. In this research, there were 12 positions/points of gibbon sleeping trees at the Soraya research station. The following is a track image of the position of the gibbon tree sleeping during the research, which can be seen in Figure IV.1.